External Biomedical Device Relaying BSN Scheme - Xidong Zhang; Guixia Kang; Ping Zhang; Heng Zhang; Xiangyi Li (Institute of Advanced Engineering and Science, 2013)
Biological parameters acquiring devices are very important in Ubiquitous Medical/Health Care system as they are responsible for gathering physical parameters for further analyze. It is natural that they form a wireless network when they transmit the collected data, and the network is referred to as BSN. Energy efficiency is vital in BSN because that the replacement of power resources of the devices implanted in human body is extremely costly. Considering the difference between In-body channel and special channel, a novel BSN transmission scheme, Coop BSN, is proposed in this paper. In Coop BSN, The transmission of IBDs is divided into two steps as the external devices are treated as relays. The first step is the IBD-EEBD transmission, in which IBDs transmit the data they collected with modified cooperative algorithm, DDF. The second step is EEBD-Coordinator transmission, in which multiuser diversity is exploited. With the division of the transmission, the overall transmission energy efficiency is optimized. Theoretical analyze and experimental results showed that, the scheme can prolong the life time of devices, especially devices implanted in human body in BSN, which improve the feasibility of BSN. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3722